Polymorphism of the Major Histocompatibility Complex and Genetic Structure of Southern African Village Chicken Populations - Ncube, K.T.; Jooste, P.J.; Soma, P.; Dzomba, E.F.; Muchadeyi , F.C. (International Journal of Poultry Science, 2014)
The chicken Major Histocompatibility Complex (MHC) is a cluster of 19 genes spanning 92 kb on chromosome 16 and plays an important role in immune response. It is highly polymorphic and has been used to study adaptive genetic diversity in chickens. LEI0258 micro satellite marker that is on the BF region of the MHC and was used to investigate adaptive genetic diversity and population structures of village chickens from South Africa (n = 77), Zimbabwe (n = 60) and Malawi (n = 30). These village chickens are raised under scavenging production systems that are characterized by frequent exposure to diseases pathogens as well as fluctuations in feed supplies. The number of alleles, allele frequency and heterozygosity levels were used to measure diversity within populations whilst the Wright’s fixation indices were used to analyze the level of population sub-structuring. A total of 22 alleles ranging from 188-448 bp were observed. Number of alleles averaged 12 per population. Allele frequency ranged from 1.6-37.5% and HO averaged 0.5. Wright’s F statistics indicated high level of within population variability and absence of population sub-structuring amongst the South African, Malawian and Zimbabwean chickens. It was therefore concluded that LEI0258 is highly polymorphic and could be a useful marker for Southern African village chicken populations.